ANALYSIS OF THE ACTION OF RACISM ON THE HELP FILM DIRECTED BY TATE TAYLOR - Damara Komala Padma; Senja Yustitia; Siti Fathonah (The Indonesian Journal of Communication Studies, 2020)
Racism is a problem that has existed throughout the world since ancient times. Indonesia also does not escape the issue of racism. From the small issues that we did not realize until the big problems involving many parties. This racism makes the atmosphere uncomfortable and conducive if it has to involve many parties. Therefore, many filmmakers who try to raise the theme of racism become a film. This study's problem is how the movie, especially those related to forms of racism. From the formulation of this problem, this study aims to find out the contents of the film The Help, especially those related to forms of acts of racism. This study uses the content analysis method with the data validity technique is reliability testing. Based on the results of the study, it is known that the film The Help contains many acts of racism. In the scene of discrimination and prejudice dominated by actions taken by white figures to blacks. The response to this attitude of racism gave rise to hatred also fear—the scene dominated by black characters' treatment to white people. The scene of the rules made for black characters also appeared. At the same time, violence and prohibition are dominated by actions to fellow race. The act of racism appears more in the middle part of the film.